Assessing the need for a question prompt list that encourages end-of-life discussions between patients with advanced cancer and their physicians: A focus group interview study. Issue 4 (August 2022) - Sato, Ayako; Fujimori, Maiko; Shirai, Yuki; Umezawa, Shino; Mori, Masanori; Jinno, Sayaka; Umehashi, Mihoto; Okamura, Masako; Okusaka, Takuji; Majima, Yoshiyuki; Miyake, Satoshi; Uchitomi, Yosuke
Abstract: Objective: Early integration of palliative and cancer care improves the quality of life and is facilitated by discussions about the end of life after cessation of active cancer treatment between patients with advanced cancer and their physicians. However, both patients and physicians find end-of-life discussions challenging. The aim of this study was to assess the need for a question prompt list (QPL) that encourages end-of-life discussions between patients with advanced cancer and their physicians. Methods: Focus group interviews (FGIs) were conducted with 18 participants comprising 5 pancreatic cancer patients, 3 family caregivers, 4 bereaved family members, and 6 physicians. Three themes were discussed: question items that should be included in the QPL that encourages end-of-life discussions with patients, family caregivers, and physicians after cessation of active cancer treatment; when the QPL should be provided; and who should provide the QPL. Each interview was audio-recorded, and content analysis was performed. Results: The following 9 categories, with 57 question items, emerged from the FGIs: (1) preparing for the end of life, (2) treatment decision-making, (3) current and future quality of life, (4) current and future symptom management, (5) information on the transition to palliative care services, (6) coping with cancer, (7) caregivers' role, (8) psychological care, and (9) continuity of cancer care. Participants felt that the physician in charge of the patient's care and other medical staff should provide the QPL early during active cancer treatment. Significance of results: Data were collected to develop a QPL that encourages end-of-life discussions between patients with advanced cancer and their physicians.